ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA INDUSTRI TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Lestari, Adria Wuri (JUMANJI (JURNAL MANAJEMEN JAMBI), 2019)
This study is performed to examine the financial performance of the largest telecommunication companies in Indonesia that are listed in BEI. The population in this study were 11 companies Insurance sectors listed on the Stock Exchange for 5 years (2012-2015). Sampling technique used here is purposive sampling. The data is obtained based on Indonesian Capital Market Directory (ICMD 2012 and 2015) publication. It is gained sample amount of 7 companies from 11 Insurance companies those are listed in BEI.      The comparison analysis method is used to assess financial performance and stock prices, and statistical methods, the method regression to analyze the influence of the ratio of the financial data derived from Indonesian Stock Exchange (BEI) from 2012 until 2016, the price of the shares.     The results of hypothesis testing in this study indicate that (1) partially only variables of Return On Invesdtment that have singnificance effects on Stock Price. But simultaneously all independent variables has significance effect on Stock Price of the Telecommunication sectors are listed in BEI, On this research, (2) ROI shows the most influencing variable toward Stock Price that pointed  by the amount of coefficients determinan value is 36.12%. (3) The statistical of F-test shows that all independent variables simultaneously influence DPR at the adjusted determinant coefficient (R) suqure value is 58,2% its shows that research independent variables able to explain to Stock Price while the remaining of 72,6 % explained by independent variables that were un-research.